Is there evidence for the use of FLT3 inhibitors as maintenance therapy in AML?. Issue 1 (March 2021) - Levis, Mark
Abstract: It is often assumed that all patients with FLT3 (FMS-Like Tyrosine kinase-3)-mutated AML who undergo an allogeneic transplant should receive maintenance therapy with a FLT3 inhibitor. The validity of this assumption is controversial.